Exposure to dust and respiratory health among Australian miners - Rumchev, Krassi; Van Hoang, Dong; Lee, Andy (Springer Nature, 2022)
Purpose: Occupational exposure to dust has been recognised as a significant health hazard to mine workers. This study aimed to investigate the association between exposure to inhalable (INH) and respirable (RES) dust and respiratory health among mine workers in Western Australia using an industry-wide exposure database.